A retrospective analysis of the haemodynamic and metabolic effects of fluid resuscitation in vietnamese adults with severe falciparum malaria - Hoan Phu Nguyen (2018)
Background: Optimising the fluid resuscitation of patients with severe malaria is a simple and potentially cost-effective intervention. Current WHO guidelines recommend central venous pressure (CVP) guided, crystalloid based, resuscitation in adults. Methods: Prospectively collected haemodynamic data from intervention trials in Vietnamese adults with severe malaria were analysed retrospectively to assess the responses to fluid resuscitation. Results: 43 patients were studied of whom 24 received a fluid load. The fluid load resulted in an increase in cardiac index (mean increase: 0.75 L/min/m 2 (95% Confidence interval (CI): 0.41 to 1.1)), but no significant change in acid-base status post resuscitation (mean increase base deficit 0.6 mmol/L (95% CI: -0.1 to 1.3). The CVP and PAoP (pulmonary artery occlusion pressure) were highly inter-correlated (r s = 0.7, p & 0.0001), but neither were correlated with acid-base status (arterial pH, serum bicarbonate, base deficit) or respiratory status (PaO 2 /FiO 2 ratio). There was no correlation between the oxygen delivery (DO 2 ) and base deficit at the 63 time-points where they were assessed simultaneously (r s =-0.09, p=0.46). Conclusions: In adults with severe falciparum malaria there was no observed improvement in patient outcomes or acid-base status with fluid loading. Neither CVP nor PAoP correlated with markers of end-organ perfusion or respiratory status, suggesting these measures are poor predictors of their fluid resuscitation needs. © 2011 Phu et al.